Immigration Civil Service Investigator Authority in Implementing Investigation and Investigation as Law Enforcement Efforts on Immigration Criminal Actions - Ridha Nikmatus Syahada; Muhammad Azzam Alfarizi (Journal of Law and Border Protection, 2019)
Monitoring international human mobility through cross-border countries in terms of immigration has various implications for a country's survival. Immigration has a vital function in supervising and implementing the law on the traffic of foreign nationals and inhabitants of their own country in order to compensate for the threat that enters a country's territory. Immigration law enforcement is carried out both administratively and pro-judicially in its application. An Immigration Civil Servant Investigator (PPNS) is constituted in the Immigration Office to carry out its role and to deal with immigration offences that arise. This study is a descriptive analytical study of the flaws discovered with the juridical normative method employed by gathering and analyzing the literature sources gathered. Immigration Civil Servant Investigators are legally liable for their investigative acts in line with the applicable rules and regulations when conducting investigations, while official responsibilities are carried out hierarchically. Article 105 of Law Number 6 of 2011 establishes the presence of civil servant investigators, which certifies that immigration investigators are authorized to examine immigration offences committed in line with the terms of this Law. However, in its implementation, PPNS Immigration can collaborate with the National Police to carry out supervision, investigation, and investigation to optimize its supervisory and law enforcement tasks in order to help carry out both preventive and repressive law enforcement in order to build a conducive legal order